Does Chronic Kidney Disease Really Affect the Complications and Prognosis After Liver Resection for Hepatocellular Carcinoma? A Meta-Analysis - Liu, Xiao-Yu; Zhao, Zhi-Qiang; Cheng, Yu-Xi; Tao, Wei; Yuan, Chao; Zhang, Bin; Wang, Chun-Yi (Frontiers in Surgery, 2022)
Purpose: The purpose of the meta-analysis was to analyze whether chronic kidney disease (CKD) affected the complications and prognosis after liver resection for hepatocellular carcinoma. Methods: The PubMed, Embase and Cochrane Library databases were searched from inception to Feb 22, 2021 to find eligible studies. Complications, overall survival (OS) and disease free survival (DFS) were collected, and this meta-analysis was performed with RevMan 5.3. Results: A total of nine studies including 6541 patients were included in the current meta-analysis. After pooling up all the baseline information, CKD group had a higher rate of Child-Pugh grade B than Non-CKD group (OR=1.58, 95% CI=1.30 to 1.93, P<0.00001). As for surgery-related information, CKD group had larger blood loss (MD=-404.79, 95% CI=-509.70 to -299.88, P<0.00001), and higher rate of blood transfusion (OR=2.47, 95% CI=1.85 to 3.30, P<0.00001). In terms of complications, CKD group had a higher rate of overall complications (OR=2.10, 95% CI=1.57 to 2.81, P<0.00001) and a higher rate of ≥ grade III complications as well (OR=2.04, 95% CI=1.57 to 2.81, P=0.0002). CKD group had a poor OS compared with Non-CKD group (HR=1.28, 95% CI=1.10 to 1.49, P=0.001), however, in terms of DFS, no significant difference was found (HR=1.11, 95% CI=0.96 to 1.28, P=0.16). Conclusion: Preexisting CKD was associated with higher ratio of complications and poor OS.